STRATEGY TO MINIMIZE THE BLEEDING RISKS IN PATIENTS WITH ATRIAL FIBRILLATION WHO RECEIVE COMBINED ANTITHROMBOTIC THERAPY AFTER PERCUTANEOUS CORONARY INTERVENTION - D. A. Zateishchikov (Атеротромбоз)
The use of combined antithrombotic therapy in patients with atrial fibrillation who underwent percutaneous coronary interventions is associated with an increased risk of bleeding. In this regard, minimizing haemorrhagic risk is one of the strategic priorities in the management of this clinical group. The article is devoted to the discussion of strategies to reduce the bleeding risk in this category of patients. Particular attention is paid to the role of direct oral anticoagulants in the implementation of this strategy.